Amenities of book collecting and kindred affections - Newton, Alfred Edward (New Delhi : Lector House LLP, 2023)
The Amenities of Book Collecting and Kindred Affections is a classic guide to the world of book collecting, written by the renowned bibliophile A. Edward Newton. This charming collection of essays delves into the joys and pleasures of discovering rare and valuable books, sharing personal anecdotes and insights from the author's extensive experience. Newton discusses the history of book collecting, the importance of bookbinding and bookplate design, and the thrill of finding hidden treasures. With its engaging style and wealth of knowledge, this book is a must-read for anyone who loves books and wants to learn more about the art of collecting them.
Includes index.
Keywords: Book collecting; Book collecting; Literary history